Drug‐specific T‐cell responses in patients with liver injury following treatment with the BACE inhibitor atabecestat. Issue 6 (24th November 2020) - Thomson, Paul J.; Kafu, Laila; Meng, Xiaoli; Snoeys, Jan; De Bondt, An; De Maeyer, Dries; Wils, Hans; Leclercq, Laurent; Vinken, Petra; Naisbitt, Dean J.
Abstract: Background: Atabecestat is an orally administered BACE inhibitor developed to treat Alzheimer's disease. Elevations in hepatic enzymes were detected in a number of in trial patients, which resulted in termination of the drug development programme. Immunohistochemical characterization of liver tissue from an index case of atabecestat‐mediated liver injury revealed an infiltration of T‐lymphocytes in areas of hepatocellular damage. This coupled with the fact that liver injury had a delayed onset suggests that the adaptive immune system may be involved in the pathogenesis. The aim of this study was to generate and characterize atabecestat(metabolite)‐responsive T‐cell clones from patients with liver injury. Methods: Peripheral blood mononuclear cells were cultured with atabecestat and its metabolites (diaminothiazine [DIAT], N ‐acetyl DIAT & epoxide) and cloning was attempted in a number of patients. Atabecestat(metabolite)‐responsive clones were analysed in terms of T‐cell phenotype, function, pathways of T‐cell activation and cross‐reactivity with structurally related compounds. Results: CD4 + T‐cell clones activated with the DIAT metabolite were detected in 5 out of 8 patients (up to 4.5% cloning efficiency). Lower numbers of CD4 + and CD8 + clones displayed reactivity against atabecestat. Clones proliferated and secreted IFN‐γ, IL‐13 and cytolytic molecules following atabecestat or DIAT stimulation. Certain atabecestat and DIAT‐responsive clones cross‐reacted with N ‐acetyl DIAT; however, no cross‐reactivity was observed between atabecestat and DIAT. CD4 + clones were activated through a direct, reversible compound‐HLA class II interaction with no requirement for protein processing. Conclusion: The detection of atabecestat metabolite‐responsive T‐cell clones activated via a pharmacological interactions pathway in patients with liver injury is indicative of an immune‐based mechanism for the observed hepatic enzyme elevations. Abstract : The atabecestat diaminothiazine metabolite activates T‐cells from patients with atabecestat‐associated liver injury. CD4 + T‐cell clones are activated through a direct, non‐covalent drug (metabolite)‐HLA class II interaction with no requirement for protein processing. It is likely that the adverse reactions experienced by these patients while on treatment with atabecestat were mediated at least in part by drug‐responsive CD4 + T‐cells.